Технология подземной разработки руд - Дубынин Н. Г. Николай Григорьевич; Коваленко В. А. Виктор Андреевич; Умнов А. Е. Анатолий Емельянович; Власов В. Н. Владимир Никифорович (Москва, Недра, 1983)
Авт. указаны в вып. дан.